Maternal relationship quality and peer social acceptance as mediators between child maltreatment and adolescent depressive symptoms: Gender differences. (16th December 2017) - Alto, Michelle; Handley, Elizabeth; Rogosch, Fred; Cicchetti, Dante; Toth, Sheree
ABSTRACT: Childhood maltreatment negatively impacts the development of maternal and peer relationships and may put adolescents at risk for depression. The present study examined gender differences in maternal relationship quality and peer social acceptance as mediators of the association between childhood maltreatment and adolescent depressive symptoms in 342 (151 female, 191 male) maltreated ( n = 198) and nonmaltreated ( n = 144) youth in the USA. An observer report Q‐Scale measure of depressive symptoms was developed and received preliminary support. Social acceptance was a significant mediator for both genders. The significant association between maltreatment and maternal relationship quality was unique to females, and the association between maternal relationship quality and depressive symptoms was significantly stronger for females. Lower maternal relationship quality marginally significantly mediated the association between maltreatment and depressive symptoms for females only. Results have implications for the prevention and intervention of depression in adolescents with a history of childhood maltreatment.